Accounting knowledge for students of the Faculty of Management and Economics in cryptocurrencies and methods of disclosing them Iraqi and Jordanian universities (comparative study) - Ammar Imad Khalaf Halboosh (Scholars Digest Publishing, 2023)
The main aim of the research is to study the levels of accounting knowledge and methods of disclosure thereof among Iraqi and Jordanian students, and to indicate the possible ways of disclosure and analyze them theoretically. Where this study comes to measure the levels of knowledge of the students of the College of Administration and Economics about cryptocurrencies and methods of disclosure, and the extent of their knowledge of how to complete commercial operations using them, The research relied on the descriptive analytical approach, where a simple random sample of students of the College of Administration and Economics in Iraqi and Jordanian universities was selected and a questionnaire was distributed to the sample, and in order to analyze the data obtained, the researcher calculated the correlation coefficients (Pearson) between the degree of each axis of the questionnaire and the degree .The totality of the questionnaire, and the researcher used Cronbach's alpha coefficient to calculate the stability of the scale used in the study, where the value of the alpha coefficient was found for the axes of the questionnaire as well as for the total score of the questionnaire tool, and the study found through the practical side that there are statistically and morally significant differences between Iraqi and Jordanian students, as it confirmed .The results showed that the Jordanian students are at a better level than the Iraqi students with regard to the basic knowledge The meaning and methods of trading encrypted currencies, as well as knowledge of their characteristics. As for the methods of disclosure, it was found that there are no differences between Iraqi and Jordanian students.
Keywords: Accounting knowledge, cryptocurrencies, blockchain, cryptocurrency disclosure, cryptocurrency risks.